KARAKTERISTIK ENKAPSULAT EKSTRAK PEWARNA BUAH PANDAN (Pandanus tectorius) PADA PERLAKUAN ENKAPSULAN GELATIN DAN MALTODEKSTRIN - Yogaswara, Ida Bagus; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 4 (2017): Desember, 2017)
Pandanus fruit can be processed into a natural dye containing carotenoids by extraction and encapsulation. The aims of this study were to know the characteristic encapsulation of pandanus fruit ekstract product.. The experiments in this study used a single factor Randomized Block Design. The factors are the ratio of gelatin and maltodextrin (1: 1), (1: 1,5), (1: 2), (1: 2,5), and (1: 3). The results showed that the comparative factor of gelatin and maltodextrin had significant effect (P <0.01) moisture content, total carotenoid, surface carotenoid, efficiency of encapsulation and solubility. Characteristic of pandanus extract encapsulation with ratio gelatin and maltodextrin had moisture 6,31 - 6,79%, total carotenoid 895,08 - 1336,84 mg / 100g, surface carotenoid 468,79 - 715,94 mg / 100g, efficiency of encapsulation 19,99 - 64,93%, and solubility 77,93 - 86,37%. Key words: pandanus fruit extract, gelatin, maltodextrin, encapsulation.